2008
DOI: 10.1016/j.ccell.2007.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Directions for Disaster Nursing Education in the United States

Abstract: Because of their diverse education, experience, and practice settings, nurses are uniquely qualified to be first receivers, care givers, and leaders in any large-scale public health emergency. Many nurses, however, continue to feel inadequately prepared to function effectively in these types of situations. Great strides have been made since 2001, but much work remains to be accomplished. This article focuses on newer approaches used to teach nurses the principles of disaster preparedness. It also addresses the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 23 publications
2
46
0
Order By: Relevance
“…2004, Katz et al. 2006, Littleton‐Kearney & Slepski 2007). Previous studies have shown that nurses believe that they are poorly prepared and lack the necessary training to respond to a disaster with confidence because of a lack of knowledge or skills (Fung et al.…”
Section: Introductionmentioning
confidence: 99%
“…2004, Katz et al. 2006, Littleton‐Kearney & Slepski 2007). Previous studies have shown that nurses believe that they are poorly prepared and lack the necessary training to respond to a disaster with confidence because of a lack of knowledge or skills (Fung et al.…”
Section: Introductionmentioning
confidence: 99%
“…The professional preparedness of nurses is undoubtedly crucial [4] in providing health services for the injured, as they are often considered to be in the front line of healthcare provision [3][4][5][6]7]. Given the negative impacts of disasters on public health and welfare, providing proper health services is the main factor contributing to the survival, reduced mortality and well-being in people affected by the events [8].…”
Section: Introductionmentioning
confidence: 99%
“…Given the growing number of incidents and disasters, health service providers play a key role before, during and after these events and their preparedness is crucial [1][2][3]. The professional preparedness of nurses is undoubtedly crucial [4] in providing health services for the injured, as they are often considered to be in the front line of healthcare provision [3][4][5][6]7].…”
Section: Introductionmentioning
confidence: 99%
“…27,35 A recent survey of faculty in baccalaureate nursing programs in Louisiana indicated that although faculty felt mass casualty incident education was important, most lacked the training and experience to teach such a subject. The current emergency and disaster core competencies for both public health and hospital nurses don't address all skill sets, and they haven't been validated.…”
Section: Thinking Outside Of the Boxmentioning
confidence: 99%